Gene expression analysis exposes mitochondrial abnormalities in a mouse model of Rett syndrome. - Kriaucionis, S; Paterson, A; Curtis, J; Guy, J; Macleod, N; Bird, A (2006)
Rett syndrome (RTT) is a severe neurological disorder caused by mutations in the X-linked MECP2 gene, which encodes a methyl-CpG binding transcriptional repressor. Using the Mecp2-null mouse (an animal model for RTT) and differential display, we found that mice with neurological symptoms overexpress the nuclear gene for ubiquinol-cytochrome c reductase core protein 1 (Uqcrc1). Chromatin immunoprecipitation demonstrated that MeCP2 interacts with the Uqcrc1 promoter. Uqcrc1 encodes a subunit of mitochondrial respiratory complex III, and isolated mitochondria from the Mecp2-null brain showed elevated respiration rates associated with respiratory complex III and an overall reduction in coupling. A causal link between Uqcrc1 gene overexpression and enhanced complex III activity was established in neuroblastoma cells. Our findings raise the possibility that mitochondrial dysfunction contributes to pathology of the Mecp2-null mouse and may contribute to the long-known resemblance between Rett syndrome and certain mitochondrial disorders.